2011
DOI: 10.1002/art.30401
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐C1q antibodies are associated with systemic lupus erythematosus global activity but not specifically with nephritis: A controlled study of 126 consecutive patients

Abstract: Objective. Several studies have shown that antiC1q antibodies correlate with the occurrence and activity of nephritis in systemic lupus erythematosus (SLE). However, the significance of anti-C1q antibodies in SLE has not been fully characterized. The aim of this study was to investigate associations between anti-C1q antibodies and clinical and serologic parameters of SLE.Methods. An enzyme-linked immunosorbent assay kit was used to measure anti-C1q antibodies in the sera of 126 consecutive patients with active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 30 publications
4
46
1
Order By: Relevance
“…In the diagnosis of SLE high titers of Ro-SSA [40], dsDNA [41] and C1q [42] specific IgG autoantibodies are considered among the most specific markers, while ssDNA specific IgG appears in many inflammatory disorders and in normal subjects as well [43]. In our experiments, comparing detection of immune complexes by secondary antibodies against human IgG and IgM with U937 cells, we found positive correlation between cell and IgG but not IgM signals (Table 1).…”
Section: Discussionsupporting
confidence: 54%
“…In the diagnosis of SLE high titers of Ro-SSA [40], dsDNA [41] and C1q [42] specific IgG autoantibodies are considered among the most specific markers, while ssDNA specific IgG appears in many inflammatory disorders and in normal subjects as well [43]. In our experiments, comparing detection of immune complexes by secondary antibodies against human IgG and IgM with U937 cells, we found positive correlation between cell and IgG but not IgM signals (Table 1).…”
Section: Discussionsupporting
confidence: 54%
“…Anti-dsDNA antibodies have been widely used as a clinical biomarker of LGLN occurrence or relapse [17,18]. Furthermore, anti-C1q antibodies have recently emerged as perpetuators of renal inflammation [19][20][21][22], yet their pathogenetic potential is currently being challenged [23][24][25]. Unfortunately, no reliable biomarkers able to predict LGLN in SLE patients have been identified to date [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that levels of anti-C1q antibodies decreased after successful treatment of lupus nephritis [25]. However, these findings are in contrast to data found by Katsumata et al describing that anti-C1q antibodies were associated with SLE global disease activity but not specifically with active lupus nephritis [26]. Taken together, the value of anti-C1q in SLE patients as follow-up marker is controversial and data on the correlation between anti-C1q levels and changes in disease activity within individual patients are lacking.…”
Section: Introductionmentioning
confidence: 87%